Divergent predation environment between two sister species of livebearing fishes (Cyprinodontiformes: Poeciliidae) predicts boldness, activity, and exploration behavior - Money, David Andrus (2017)
Predators can influence a variety of prey traits, including behavior. Traits such as boldness, activity rate, and tendency to explore can all be shaped by predation risk. Our study examines the effects of predation on these behaviors by considering a natural system in which two sister species of livebearing fishes, Brachyrhaphis roseni and B. terrabensis, experience divergent predation environments. In February of 2013, we collected fish in the Río Chiriquí Nuevo drainage, Chiriquí, Panama, and conducted behavioral assays. Using open-field behavioral assays, we evaluated both juveniles and adults, and males and females, to determine if there were differences in behavior between ontogenetic stages or between sexes. We assessed boldness as ‘time to emerge’ from a shelter into a novel environment, and subsequently measured activity and exploration within that novel environment. We predicted that B. roseni (a species that co-occurs with predators) would be more bold, more active, and more prone to explore, than B. terrabensis (a species that does not co-occur with predators). In total, we tested 17 juveniles, 21 adult males, and 20 adult females of B. roseni, and 19 juveniles, 19 adult males, and 18 adult females of B. terrabensis. We collected all animals from streams in Chiriquí, Panama in February 2013, and tested them following a short acclimation period to laboratory conditions. As predicted, we found that predation environment was associated with several differences in behavior. Both adult and juvenile B. roseni were more active and more prone to explore than B. terrabensis. However, we found no differences in boldness in either adults or juveniles. We also found a significant interaction between ‘sex’ and ‘species’ as predictors of boldness and exploration, indicating that predation environment can affect behaviors of males and females differently in each species. Our work demonstrates the importance of considering sex and life history stage when evaluating the evolution of behavior.